Indigenous foods of Tamil Nadu-A narrative review of its nutritive value and Mineral Bioavailability - Lakshmanakumar.V,; Arthi.G,; Rathinam.J, (International Journal of Ayurveda and Pharma Research, 2024)
The Siddha system is one of the oldest traditional and holistic systems practiced in the southern part of India. “Food itself is Medicine and Medicine itself is Food” same indicates the Tamil quote “Unavae Marunthu, Marunthae Unavu” indigenous food is which is traditionally transferred from one generation to the next generation hence these food products are known as traditional foods. Indigenous food system helps to improve the quality of life. We conducted a literature search in scientific databases: PubMed and Google Scholar, also relevant Siddha literature from Dr. Ambedkar Library, Chennai. To identify studies reporting nutritive values and/or anti-nutrient content of IFs (not included in the Indian food composition database), consumed by peoples of Tamil Nadu. Data were selected and gathered from a total of 10 kinds of literature and 55 research papers. Some indigenous food displayed high levels of nutrients and minerals. Hence, efforts are desirable to encourage the inclusion of these nutritionally superior traditional foods into the usual diets. Indigenous food preparations are rich in nutraceutical compound which aids in better well-being and improve immunity. So, it is important to record indigenous foods in order to safeguard and maintain our traditional knowledge.